Beyond the ‘Uh-Oh’ Moment: Refusal Strategies in a Young EFL Learner’s Extensive Reading Responses - Zalva Fajhira Shabrina Putri; Utami Widiati; Evynurul Laily Zen (ETERNAL (English Teaching Journal), 2025)
Understanding refusal strategies utilized by young learners in learning English as a foreign language (EFL) is essential for teachers to foster more effective interaction in the classroom. The present study explores how a young EFL learner applies refusal strategies when interacting during extensive reading (ER) activities. Data were collected through real-time observations, the learner’s diaries, and a parent interview, and further analyzed using thematic analysis. The findings revealed how the young EFL learner applied more direct refusals, influenced by the learner’s developmental traits. Indirect refusals, which appeared mostly as avoidance, emerged frequently only during the initial ER sessions. Refusals, regardless, did not appear as frequent towards the end of ER sessions as the learner became comfortable and confident with the teacher’s scaffolding. Considering the findings, the current study suggests future studies to investigate how refusal strategies are applied by young EFL learners in a larger group, which may be influenced by different developmental traits, learning situations, and language proficiencies, to further generalize the findings.